PENGARUH PERJANJIAN INTERNASIONAL TERHADAP PERUBAHAN-PERUBAHAN KUHP BERKAITAN DENGAN TINDAK PIDANA AERIAL HIJACKING - Johny, Ruby Hadiati (Jurnal Dinamika Hukum, 2008)
International Agreement is very important for growth of national law, especially national criminal law. International Agreement as one of legal source can give information about growth at national law that carried out bilateral conventions and multilateral.  The growth of Criminal law in Indonesia is influenced by many growths of international society. This influence is progressively with existence of globalization that affecting at changes of behavior which outwardly shift in law orders.  Globalization era have supported by information technology, transportation and communications. One of fast transportation is plane. ICAO as world organization that concern in problem of air transportation said that this transportation is gristle with danger by people with various motifs.  Conventions that carried out by ICAO such as Convention of Tokyo year 1963, Convention of Hague year 1970, Convention of Montreal year 1971 that influenced at KUHP after Indonesia have applicator this application can see in Law No. 4 Year 1976 that concerning Hijacking. Kata kunci: Perjanjian Internasional sangat berpengaruh terhadap perubahan hukum pidana  khususnya KUHP